Nest Stuctures in Bornean Orangutan - Prasetyo, Didik; Utami, Sri Suci; Suprijatna, Jatna (JURNAL BIOLOGI INDONESIA, 2012)
Struktur Sarang Orangutan Kalimantan. Nest-building techniques processes related partiesin choosing the trees, the basic building structure, making layers, and adding nest lockingsystem with accessories. There are Lacks of data about the pattern of the orangutan nest andonly van Schaik (1995) described four Variations of nest structure. By Following 22 orangutanswith instantaneous focal animal method, 19 vertical nest structures are found, and horizontallyvariations orangutan nest forming butterfly pattern. Tree species are Elaocarpus mastersiithat mostly used by Orangutan to build nest with type of branch direction and height of firstbranch as the Reasons. Nest was built in 5-9 meters height and they were seldom to rebuilt orreuse old nest. They seldom to develop their nest in the last fruit trees to avoid nightpredators.Kata Kunci: Orangutan, Struktur dan pola, sarang.